2016
DOI: 10.25011/cim.v39i6.27489
|View full text |Cite
|
Sign up to set email alerts
|

Peak troponin I level predicts new-onset atrial fibrillation in patients with myocardial infarction

Abstract: Purpose: We aimed to assess the predictive value of peak troponin I level for the occurrence of new-onset AF in myocardial infarction. Methods: A total of 1553 patients, who were hospitalized with diagnosis of STEMI and underwent primary PCI, were retrospectively evaluated. New-onset AF was defined as any newly diagnosed AF that occurred during index hospitalization after primary PCI. Results: New-onset AF was observed in 90 patients (5.8% of the study population). Patients who developed AF were older (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Zehir [21] NA NA Karataş [22] NA 27 vs. 5%, P < 0.001. HR: 2.20 (95% CI 1.03-4.72), P = 0.040 Olsen [23] NA NA Garg [24] 10.3% vs 9.4%.…”
Section: Namentioning
confidence: 96%
See 4 more Smart Citations
“…Zehir [21] NA NA Karataş [22] NA 27 vs. 5%, P < 0.001. HR: 2.20 (95% CI 1.03-4.72), P = 0.040 Olsen [23] NA NA Garg [24] 10.3% vs 9.4%.…”
Section: Namentioning
confidence: 96%
“…The studies found a predictive relationship between laboratory parameters and subsequent incidence of NOAF. A strong association was found with elevated cardiac biomarkers including troponin and BNP [17,21,26,31,32]. Various hematological indices were regarded as predictors of the NOAF development [21,22,32].…”
Section: Predictors Of New-onset Afmentioning
confidence: 98%
See 3 more Smart Citations